Comparison of Ligasure versus Bipolar Diathermy Tonsillectomy - Wahid Saleem, Saeed Khan, Shahid Ali, Muhammad Ilyas, Adeel Niaz, Shehbaz Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the operational time, blood loss and consequences of tonsillectomy with Ligasure versus bipolar diathermy. Methods: A total of 106 individuals were randomized to have their Tonsillectomy done with either Ligasure or bipolar diathermy in this prospective trial. The length of procedure, amount of blood lost during it, degree of post-operative pain and the outcomes all were documented and studied. Results: In total, 106 cases were studied, with 53 cases in to the Ligasure Group and 53 cases to Bipolar Tonsillectomy Group. During surgery, bipolar diathermy group lost more amount of blood. The Ligasure group had an average operative time of 4 minutes less. Both groups had similar degrees of postoperative pain. Despite the fact that the Ligasure group had less postoperative hemorrhages than the diathermy group, there was no statistically significant difference. Conclusions: Study concluded that tonsillectomies using ligasure took longer than those with bipolar diathermy. Both groups had similar perioperative hemostasis. The rate of postoperative bleeding was higher than anticipated. Keywords: Ligasure, bipolar diathermy hemorrhage, hemostasis, blood loss during surgery